Pemanfaatan Biji Labu Kuning (Cucurbita Moschata) Sebagai Sumber Minyak Nabati Menggunakan Metode Ekstraksi Soxhletasi - Rina Julianty; Eka Kurniasih; Muhammad Sami (Politeknik Negeri Lhokseumawe, 2021)
Vegetable oils obtained from nuts and seeds have superiority in terms of food. They have a distinctive taste and healthy nutritional content because they contain unsaturated fatty acids, carotenoids, and flavonoids. This study aims to improve the yield of pumpkin seed oil and compare it with SNI (3741-1995) concerning cooking oil. The extraction was carried out using the soxhlet method with a temperature of 68-70ºC using hexane as a solvent and a ratio of the solvent ratio (1: 6); (1: 8); (1:10); (1:12); (1:14) (w / v) and the amount of circulation used 15; 20; 25; 30; 35. After the extraction process is evaporated to evaporate the solvent and obtain concentrate at 70ºC. The results showed a yield of 56.40%. The oil produced has physical characteristics including Specific Gravity: 0.97 gr/ml, Water Content: 6%, Boiling Point: 210ºC, Acid Number 6 mg NaOH / g, Peroxide Number: 50 meq /O2 kg, Weaving Numbers 308.55 mg KOH / g, as well as the chemical characteristics of the test results: Based on chromatographic analysis it is known that the composition of fatty acids in pumpkin seed oil is dominated by Palmitic Acid (C: 16) of 16.6736; Linoleic Acid (C: 18-2) of 53.5392; Stearic Acid (C: 18) 29.7872%. But this pumpkin seed oil has not fulfilled SNI especially cooking oil (3741-1995).